Green Learning Revolution: Needs Analysis of Engineering Design Process-Based E-LKPD for Pineapple Waste Biogas in Senior High School - Rahmi Andini; Saparini Saparini (Berkala Ilmiah Pendidikan Fisika, 2026)
This study aims to analyze the need for developing Physics E-LKPD (e-student worksheet) based on the Engineering Design Process (EDP) within the context of utilizing pineapple waste as biogas as an alternative renewable energy. The background of this study is based on physics learning that lacks context and low student learning independence. This study uses a quantitative descriptive approach involving 63 students from grades X and XI at State Senior High School 6 Prabumulih. Data was collected to identify the learning conditions and needs of students in physics education. The findings show that most students have access to digital devices and internet connectivity; however, physics learning resources are still dominated by conventional printed teaching materials, and the implementation of E-LKPD is not yet optimal. Nevertheless, students showed a high level of interest in the topic of renewable energy and responded positively to project-based learning contexts. These findings reveal a gap between students' digital readiness and the availability of interactive and innovation-oriented teaching materials. Therefore, this study aims to develop E-LKPD based on the Engineering Design Process (EDP) in the context of biogas from pineapple waste to support independent learning, improve critical thinking skills, and foster awareness of renewable energy innovation. The implications of this study indicate that the integration of EDP-based E-LKPD Physics and local wisdom, such as the use of pineapple waste to produce biogas, can increase students' independence in learning, critical thinking, and environmental awareness, as well as support curriculum development, learning practices, and real-world problem solving that are relevant to the potential of the region.